Association between the risk of relative energy deficiency in sport and cholesterol levels in Finnish endurance athletes - Silvennoinen, J. I. K.; Sipilä, P. N.; Valtonen, M.; Mjøsund, K.; Kinnula V.; Hirvelä, L.; Mierlahti, L.; Ilhalainen, J. K. (BMJ Open Sport & Exercise Medicine, 2025)
Background Relative energy deficiency in sport (REDs) is a condition caused by chronic and/or severe low energy availability. Endurance athletes are at risk of REDs, which are characterised by negative effects on health and performance. Disturbed cholesterol metabolism is a suggested indicator of REDs and could affect the future cardiovascular health of athletes. We investigated the association between the REDs risk and cholesterol levels in endurance athletes.